KAJIAN TERJEMAHAN ARTIKEL FLEEING TERROR, FINDING REFUGE DAN TERJEMAHANNYA MENCARI TEMPAT BERLINDUNG DALAM HAL STRUKTUR DAN POLA PENGEMBANGAN TEMA (PENDEKATAN LINGUISTIK SISTEMIK FUNGSIONAL) - Satriya Bayu Aji; Mangatur Nababan; Tri Wiratno (PRASASTI: Journal of Linguistics, 2017)
This research aims to describe: (1) the March 2015 National Geographic article Fleeing Terror, Finding Refuge and its March 2015 National Geographic Indonesia Indonesian translation Mencari Tempat Berlindung’s thematic structure and progression, (2) the translation techniques employed and its effect on the translation’s thematic structure and progression, and (3) its effect on the translation quality. This study belongs to the qualitative research at the descriptive level, employs embedded case study approach, and focuses on the translation product. The data consist of the Themes of the National Geographic Maret 2015 article Fleeing Terror, Finding Refuge and its National Geographic Indonesia Maret 2015 Indonesian translation Mencari Tempat Berlindung collected through content analysis and the result of the informant’s translation quality assessment collected through questionnaire and focus group discussion. This study revealed that the translation employs more marked Topical Theme than the source text and the percentage of the translation’s Rheme-based progressions (the simple linear and split Rheme progression) is higher than the source text’s. The thematic structure shifts—mostly a shift from the unmarked to the marked Topical Theme and vice-versa or a change in the Topical Theme constituent—can be caused by the use of these six translation techniques: transposition, modulation, reduction, amplification, established equivalent, and particularization. Of these six, particularization does not cause any Thematic progression shift. These six techniques that can cause a shift in the Thematic structure can also decrease the translation’s quality. Keywords: Thematic structure, Thematic progression, translation techniques, translation quality assessment